Penentuan Top Kampanye Pemasaran Menggunakan Social Network Analysis pada Shopee dan Tokopedia di Media Sosial Twitter - Prabhawa, M Dikky; Dona Rahayu; Susi (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
The increasing number of internet users in Indonesia has an impact on the magnitude of public interest in doing online shopping so that there is competition from business people to get top of mind in the community, one way to get top of mind, business people must strengthen their brand. In strengthening brands, the use of social media is one of the things used by business people today, so many marketing campaigns have sprung up so that brands can be known by consumers. To measure the achievement of a marketing campaign, it can generally be seen from the transactions that occur during the marketing campaign, but other than that it can also be done by seeing how many people talk about the marketing campaign on social media. This study uses the Social Network Analysis method to see the top marketing campaigns from Tokopedia and Shopee from public conversations on Twitter social media, namely #ShopeeGajian and #TokopediaWIB. This research data collection was taken using the Netlytic website with a data collection period when the two e-commerce marketing campaigns were run, namely 20-30 April 2021. The results showed that the top campaign from Social Network Analysis formed on Twitter #TokoPediaWIB was superior. Because the most talked about by the public.